A Review on Additive Manufacturing Processes - Pandey, Rohit (Journal of Polymer and Composites (JoPC), 2025)
Additive manufacturing is a new and rapidly developing method in the business world. “Additive manufacturing process” refers to the process of creating products from layers of material. High speed printing or 3D printing is another name for this process. This manufacturing method uses no tools and can produce highly accurate products in less time. A rigid part can be formed and used in this way. Stereolithography (STL) files are created by converting computer aided design (CAD) files used in the additive manufacturing process to these files. Drawings created with CAD are approximated with triangles and divided into sections in the process, each section containing information about the different operations to be printed. Relevant production processes and applications are discussed. They can be used to make lighter models that will save money and benefit the airline industry. Jobs in both architecture and medicine changed due to increased production. However, a lot of work and research still needs to be done before the production of additional equipment can take place in production, because not all common equipment can be used successfully. Accuracy must be improved to eliminate the need for processing steps. The continued rapid growth since launch and the positive results to date give us hope that increased production will play an important role in future production.
uGDX
Keywords: Additive manufacturing (AM); 3D printing; STL; CAD; Polymer; Prototyping